Contribution of dehydration to END in acute ischemic stroke not mediated via coagulation activation. Issue 6 (25th April 2019) - Shi, Zhu; Zheng, Wei C; Yang, Heng; Fu, Xiao L.; Cheng, Wei Y.; Yuan, Wei J.
Abstract: Objective: Dehydration is a risk factor for early neurological deterioration (END) after ischemic stroke, yet the underlying mechanism is unclear. Outbalanced coagulation activation may contribute to ischemia progression, concurrently with dehydration‐induced blood viscosity change. We aimed to investigate whether the contribution of dehydration to END was mediated by blood coagulation activation. Methods: We retrospectively evaluated consecutive patients presenting with mild or moderate stroke (National Institutes of Health Stroke Scale score ≤14) within 24 hr of onset between Jan 2016 and Dec 2017. Dehydration was defined by a serum nitrogen to creatinine ratio (BUN/Cr) of ≥15 and blood coagulation activity was assessed with thromboelastography (TEG). The correlations between BUN/Cr and TEG parameters were assessed and their relationship in the development of END was analyzed. Results: Of 244 patients, 64 (26.2%) developed END within 3 days after admission. Patients with END had significantly higher BUN/Cr (19.2 ± 5.7 vs. 15.3 ± 2.9, p  = 0.008), shorter R and K on TEG test (R: 3.9 ± 1.0 vs. 4.6 ± 1.1, p  = 0.001; K: 1.3 ± 0.5 vs. 1.5 ± 0.4, p  = 0.005). Comparison between patients with and without dehydration revealed no significant differences in TEG parameters. Multivariate regression suggested that dehydration status (OR 3.91, 95%CI 2.17–8.67, p  = 0.008) and shorter R tercile on TEG (OR 3.18, 95% CI 1.23–7.90, p  = 0.016) were independently associated with END; however, the odds ratio of R for END remained unchanged after adjustment for dehydration status. Conclusion: Our findings suggested that the contribution of dehydration to END after ischemic stroke was mediated by blood coagulation activation. Abstract : Dehydration and blood hypercoagulability is common among patients with acute ischemic stroke. Blood hypercoagulability measured with thrombelastography( TEG) is not correlated with dehydration status. Both dehydration and hypercoagulability are independently associated with early neurological deterioration(END) after stroke.